Placenta Previa Prevalence and Risk Factors in Women Undergoing Cesarean Sections : Prevalensi dan Faktor Risiko Placenta Previa pada Wanita yang Melakukan Operasi Caesar - Ebtihal Sattar Qassim; Douaa Aziz , Douaa Aziz Darfash; , Maitham Abed Shawwat (Academia Open, 2026)
General Background Placenta previa is a major obstetric condition associated with antepartum hemorrhage and adverse maternal and neonatal outcomes. Specific Background Rising cesarean section rates and increasing maternal age have contributed to higher reported cases, particularly in high-risk hospital settings. Knowledge Gap Limited region-specific data are available regarding placenta previa prevalence and maternal risk factors among women undergoing cesarean delivery in Iraq. Aims This study aimed to estimate the prevalence of placenta previa and identify associated maternal risk factors among cesarean deliveries in AL-Muthanna and AL-Diwaniya, Iraq. Results A retrospective cross-sectional analysis of 300 cesarean deliveries identified placenta previa in 15% of cases, with advanced maternal age, multiple previous cesarean sections, high parity, elevated body mass index, anterior placental location, and comorbidities showing significant associations. Novelty This study provides stratified regional evidence linking surgical history and maternal characteristics to placenta previa within a high-cesarean population. Implications Early identification of high-risk women may support tailored antenatal surveillance and surgical planning to reduce maternal complications. Keywords: Placenta Previa, Cesarean Section, Maternal Age, Obstetric Risk Factors, Pregnancy Complications Key Findings Highlights: Placenta previa was identified in a notable proportion of cesarean deliveries within the study population. Advanced maternal age and repeated surgical deliveries showed strong statistical associations. Stratified analysis clarified maternal and placental characteristics linked to higher clinical risk.